Forging sustainable futures: UiTM Perak’s Green Delegation to Chulalongkorn University in Thailand / Farihana Abdul Razak - Abdul Razak, Farihana (Universiti Teknologi MARA, Perak, 2024)
8 July 2024 – The pressing need for sustainable development and environmental conservation has prompted educational institutions worldwide to take proactive measures. Universiti Teknologi MARA (UiTM) Perak Branch, through its Green Campus and Gresafe Cities initiatives, has been at the forefront of promoting sustainable practices.